(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
MDMBP Carwash in a Café was conceptualized by the researchers in 2019. The business concept was all about offering services and products that will enrich customer satisfaction, especially for car owners and drivers. The importance of this business is to fulfill the problem and needs of customers about carwash, particularly to meet also customer’s contentment by offering different kinds of carwash and detailing services. The significance of this business was to comply with customer’s gratification by offering different features within products and services, such as packages, discounts, and freebies. The researchers used a descriptive research method for the survey to collect the customers’ perceptions about the business concept. The survey will determine if the business concept is approved and if it is feasible in the preferred location. The survey was answered by 50 respondents, which are composed of private car owners and drivers, public vehicle drivers, and other respondents such as parking attendants and salespeople at Banawe Street. The study also used a financial plan to analyze and predict the estimated budget, sales, and capital of MDMBP Carwash in a Café. The results of the survey showed positive perceptions from the respondents in terms of the business location; the respondents said that it was extremely suitable, especially for private and public car owners. The business was also approved by the respondent because of its uniqueness of having a café that has a special treat such as movie streaming and free WIFI, which are advantageous for car drivers or owners to stay, entertain themselves, and relax. The business is also highly acceptable because the business offers, discounts, freebies, and packages with low prices. The results of the financial statement showed a reasonable outcome. As of the first year of the business operation, the business already gained profit from the estimated sales of the product and services. Simultaneously, the return on investment was also well-founded because it produced 11% from the first year of operation. The researchers discovered that MDMBP Carwash in a Café is extremely acceptable and accessible from the location because it was along the highway and near the auto parts station, where there is a high possibility for customers to visit and purchase any of the products and services offered.